On-line simultaneous monitoring of glucose and acetate with FIA during high cell density fermentation of recombinant E. coli - Rocha, I. (2002)
A two-channel flow injection analysis (FIA) system was developed for the simultaneous on-line monitoring of acetate and glucose during high cell density fed-batch fermentations of recombinant Escherichia coli. Acetate measurement was performed with a modified and optimised version of an existing method, based on acetate diffusion through a gas-diffusion chamber into a stream containing an acid–base indicator. The subsequent decrease in the absorbance was detected with an incorporated photometer. After method optimisation, it was possible to achieve linearity until 10 g/kg with no dilution step and with a detection level of 0.05 g/kg. Although some interferences were found, the performance of the method proved to be sufficiently reliable for on-line control purposes Commercially packed glucose oxidase (GOD) was used for the amperometric measurement of glucose. The method was linear up to 5 g/kg and it was possible to detect concentrations lower than 0.06 g/kg. For these measurements, no significant interferences were detected when the results were compared with other reference methods. The application of a simultaneous parallel configuration of the methods to a high cell density fed-batch E. coli fermentation was tested and reliable results were obtained within a 3 min delay. This information was made available to a supervisory computer running a developed LabVIEWTM programme via an Ethernet network, allowing the immediate implementation of control actions, improving the process performance.